2007
DOI: 10.1037/0021-9010.92.5.1286
|View full text |Cite
|
Sign up to set email alerts
|

The joint effects of personality and workplace social exchange relationships in predicting task performance and citizenship performance.

Abstract: This field study examines the joint effects of social exchange relationships at work (LMX:leader-member exchange and TMX: team-member exchange) and employee personality Existing research has demonstrated the importance of personality characteristics and social exchange relationships as predictors of task and citizenship performance (Barrick & Mount, 1991;Eisenberger, Fasolo, & Davis-LaMastro, 1990;Judge & Ilies, 2002;LePine & Van Dyne, 2001;Settoon, Bennett, & Liden, 1996). To date, however, consideration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
294
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(339 citation statements)
references
References 103 publications
26
294
0
8
Order By: Relevance
“…In the social exchange theory, establishing and maintaining positive relationships between interacting parties can encourage the beneficiary to give back, which enables the members in such an exchange to benefit from the relationship (Kamdar and Van Dyne, 2007). Li, Sanders, and Frenkel (2012) and Kim, O'Neill, and Cho (2010) conducted research studies on the hospitality industry and found that leaders who voluntarily provided service and assistance to encourage returns or positive responses from subordinates positively stimulated workers' investment in the jobs and their willingness to assist and support each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the social exchange theory, establishing and maintaining positive relationships between interacting parties can encourage the beneficiary to give back, which enables the members in such an exchange to benefit from the relationship (Kamdar and Van Dyne, 2007). Li, Sanders, and Frenkel (2012) and Kim, O'Neill, and Cho (2010) conducted research studies on the hospitality industry and found that leaders who voluntarily provided service and assistance to encourage returns or positive responses from subordinates positively stimulated workers' investment in the jobs and their willingness to assist and support each other.…”
Section: Resultsmentioning
confidence: 99%
“…Social exchange is a voluntary action that individuals demonstrate when they expect to obtain rewards from elsewhere (Kamdar and Van Dyne, 2007). From the perspective of social exchange, employees who expect support and assistance from their co-workers must also provide support and assistance to their co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this perspective, group communication and group cohesiveness is based on group member's assessment of the overall relationship quality and influence. The development of communication exchange and cohesiveness are more likely to occur when group members are closely connected socially, and attributions of meaning are shared at a high level (Kamdar & Van Dyne, 2007). Moreover, as above, consideration of the level of analysis at which this moderated process and associations are expected to hold is important (Yammarino et al, 2012 Hypothesis 2: The effect of cooperative communication on perceived group cohesiveness will be moderated by group members' collectivist cultural context at group level.…”
Section: Cross Level Effects Of Collectivist Cultural Contextmentioning
confidence: 97%
“…24 Interactions among peers have been suggested to initiate social exchange process, promoting reciprocal behaviour, and the social exchange relationship positively relates to task performance. 25 Virtual peer interaction plays an important role in creating a healthy self-identity for young men and women. 13 It is vital to users ' online dating experience and eventually converts registered users into paid-subscribers / members.…”
Section: Peer -Interactivity Onlinementioning
confidence: 99%